synthesis and studies of mixed-Ligand complexes of some transition Elements (Baghdad Science Journal, 2006)
I've been in this work to prepare some complexes containing mixed Kandat with some transitional elements which new complexes according to the best of our knowledge and to refer to the information from the Internet until I have been studying this diagnosis Aalmakdat